Paediatric peritoneal dialysis in a developing country: practice, challenges and opportunities (2019)
Background: The practice and challenges of peritoneal dialysis (PD) in a developing country may be uniquely different from what obtains in developed countries. Method: A review of the practice and challenges of PD in Nigeria as a case study and documentation of opportunities for improvement Review: There has been renewed interest in the provision of PD to children in acute kidney injury in Nigeria and this has led to adaptations such as use of nasogastric tubes as PD catheters and use of constituted PD fluid. The use of adaptations is lifesaving but complication rates may be higher than with the use of standard gadgets. Other challenges include limited availability and high cost of PD catheters and PD fluid. There are also challenges with the availability of expertise for the insertion of PD catheters and the PD procedure. Opportunities to advance paediatric PD include sustained efforts to provide PD with the use of adaptations, collection of data on outcomes of PD, advocacy for more support from government, non- governmental organisations and industry in the forms of insurance coverage, access to consumables and/or training in paediatric PD. Conclusion: Sustained provision of PD with adaptations, documentation of outcomes, and advocacy may lead to improvement in paediatric PD services.